Serbia Rediviva: The 1804 Memorandum of Metropolitan Stratimirović On the Creation of a Slavonic Serbian Grand Duchy - Сотировић, Владислав Б. (Slavistica Vilnensis, 2001)
In 1804, the Karlovci Metropolitan Stevan Stratimirović created the concept of an autonomous tributary Orthodox Štokavian Slavonic-Serbian state, based on a common religion and language. The state would be governed by the Russian Grand Duke, would be under the Russian political-military protectorate, would be included only nominally in the Ottoman Empire, and would pay an annual fixed tribute to the Turkish Sultan as its suzerain.Stratimirovic’s notion of a politically united Serbian nation, based on a common religion and language, and located within the borders of a single national state, anticipated unification of historical and ethnic Serbian territories from both the Ottoman Empire and the Habsburg Empire. His notion of national identification of the Serbs was quite innovative for the time. As a result, according to Stratimirovic, the Serbian nation was represented by the entire Eastern Orthodox South Slavic population that spoke the Shtokavian dialect and had for its literary language “Slavono-Serbian”. As a result, all Balkan territories settled by the Orthodox Shtokavian-speaking Serbian South Slavs were to be included in this unified Serbia.Stratimirovic’s ideas were expressed in a Memorandum submitted to the Russian Emperor Alexander I. The Memorandum made a major contribution to the development of modem Serbian political doctrines and ideologies. The Memorandum was undertaken during a turning point in Serbian history: the period of the First Serbian Uprising (1804–1813), and was one of the most influential plans of this period for Serbian emancipation and national political unification.